Low variations in anatomical characters of lowland and upland rice from Sarawak, Malaysian Borneo - Renee Priscilla Trawas, Sylvester Embuas; Freddy Yeo, Kuok San; Zazevia, Frank Clifton; Meekiong, Kalu; Zinnirah, Shabdin; Lai, Lee San (Springer Nature, 2025)
Oryza sativa L. or commonly known as rice belongs to the family of Poaceae. In Malaysia, rice is normally cultivated either as lowland or upland rice. The present study was undertaken with the objective to characterise and document the variations in anatomical traits of leaf, midrib and the root of 22 lowland and 22 upland rice accessions. The leaf, midrib and root anatomy of the lowland and upland rice accessions have the same fundamental anatomical structure. Stomata were found abundant on the abaxial surface as compared to the adaxial surface in general. It is interesting to note that the upland rice accessions, in general, had higher stomatal density on the adaxial surface. In addition, the upland rice accessions, in general, had larger root and stele diameters as compared to lowland rice accessions. The variation in root diameter is associated to the changes in the number and size or width of cortical cells and stele diameter. Wider stele may allow higher plant water status under water deficit, due to higher hydraulic conductivity. In addition, greater xylem diameter (indicated by larger stele diameters) is linked to better axial conductance, which improved rice’s ability to absorb and hold more water during water-limiting conditions. These traits are possibly advantageous for upland rice for efficient water capture, especially under water-deficit stress.